Teachers'Coordination within the Framework of the EHEA: the Case of the Faculty of Business and Tourism in Ourense - Patricio Sanchez Fernandez; Elena Rivo López; Mª Cruz del Rio Rama (Universitat Politècnica de València, 2012)
Recently, technology has been incorporated into higher education, leading to the appearance of new educational scenarios.    At the same time, this fact has set up several processes aimed at quality improvement. In this paper, we look at the teaching coordination experience carried out in the Faculty of Business Sciences and Tourism in Ourense.  This experience consisted in the ellaboration of an activity schedule that shows the main activities for subject assessment  during a semester. This experience had two main objectives: first, to facilitate the students'planning of their tasks in continuous assessment; second, to detect possible overlaps and work overloads. The Google Calendar was used to achieve these objectives, and the results obtained can be regarded as satisfactory.